The Association of Blood Transfusion with Outcome among African Children Hospitalized with Plasmodium falciparum Malaria: A Prospective Multicentre Observational Study - Ackerman, Hans (Lancet Haematol, 2020)
SUMMARY: BACKGROUND: Infection with Plasmodium falciparum leads to severe malaria and death in approximately 400,000 children each year in sub-Saharan Africa. Blood transfusion may benefit some patients with malaria but could potentially harm others. The aim of this study was to estimate the association between transfusion and death among children admitted to hospital with P. falciparum malaria. METHODS: We analyzed admissions to six tertiary care hospitals located in Banjul, The Gambia; Blantyre, Malawi; Lambaréné, Gabon; Libreville, Gabon; Kilifi, Kenya; and Kumasi, Ghana that participated in the Severe Malaria in African Children (SMAC) network. Patients were enrolled in the observational study if they were under the age of 15 years and had a blood smear positive for P. falciparum. Blood transfusion was administered at the discretion of the responsible physicians who were aware of local and international transfusion guidelines. Odds of in-hospital death associated with transfusion were estimated using site- and severity-adjusted models. Generalized additive models were used to estimate optimal hemoglobin transfusion thresholds. FINDINGS: 25,893 patients were admitted to hospital with P. falciparum malaria and enrolled in the study from December 3, 2000 through March 8, 2005. 8,513 (32·8%) of 25,893 received a blood transfusion. Patients were followed until discharge from hospital over a median (IQR) of 2 (1–4) days. Transfusion was associated with decreased odds of death in site-adjusted analysis (OR=0·82 [95%CI 0·71–0·94]) and after adjusting for the increased disease severity of transfused patients (OR=0·50 [95% CI 0·42–0·60]). Among all study participants, transfusion was associated with improved survival when the admission hemoglobin was up to 77 g/L (95% CI: 65–110). Among those with impaired consciousness, transfusion was associated with improved survival at hemoglobin concentrations up to 105 g/L (95% CI 71–115). Among those with hyperlactatemia, the association with improved survival persisted at even greater hemoglobin concentrations (lower bound of 95%CI: 90 g/L). INTERPRETATION: Whole blood transfusion was strongly associated with improved survival among children with P. falciparum malaria. Among those with impaired consciousness or hyperlactatemia, transfusion was associated with improved survival at hemoglobin concentrations above the currently recommended transfusion threshold. These findings highlight the need to conduct randomized controlled trials to test higher transfusion thresholds among African children with severe malaria complicated by impaired consciousness or elevated blood lactate.